Fiber optic state of charge sensor for vanadium redox flow batteries - Niklas Janshen and Florian Rittweger and Christian Modrzynski and Karl-Ragmar Riemschneider and Antonio Chica Lara and Thorsten Struckmann (IEEE, 2023)
The efficient operation of vanadium redox flow batteries requires a precise half cell specific measurement of the state of charge. In this work, we give the proof of concept for an alternative SoC monitoring approach in operando for both half cells by means of a fiber optical evanescent wave sensor (FOEWS). This method is based on the SoC dependent transmission losses through a fiber region in which the cladding is removed. Linear and parabolic correlations of the FOEWS signal to the SoC are found for the negative and positive half cell, respectively. A comparison to conventional UV/Vis absorbance SoC estimation shows a close correlation to the proposed method verifying the feasibility of the FOEWS approach.
Keywords: fiber optical evanescent wave sensor; in operando measurement; Optical fiber sensor; state of charge monitoring; Vanadium redox flow batteries